The truth of me : about a boy, his grandmother, and a very good dog - MacLachlan, Patricia (Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2013)
Robbie and his dog, Ellie, spend the summer at his grandmother Maddy's house, where Robbie learns many things about his emotionally distant parents and himself.